Engineering CdS buffer layer for high efficiency kesterite solar cells - Shareen Naomi (Nanyang Technological University, 2020)
Copper zinc tin sulfide (kesterite, Cu2ZnSnS4, CZTS) is a promising earth-abundant and non-toxic material for thin-film solar cells. The efficiency of CZTS solar cells can be further improved by reducing the JSC loss due to the parasitic absorption of short wavelength (<520 nm) photons in thick CdS that reduces the light absorbed by CZTS. An effective way to improve the efficiency of CZTS devices is to reduce the CdS thickness, as a thinner CdS allows more light to be absorbed by CZTS, which would improve the JSC and hence increase the efficiency. In this study, the effect of using various cadmium precursors and varying CdS deposition parameters on the device performance is investigated. External quantum efficiency (EQE) measurements show that using cadmium nitrate (Cd(NO3)2) as the precursor yields a thinner CdS layer, leading to the improvement of the device’s ability to collect carriers under short wavelength excitation. However, though short-circuit current (JSC) is increased by 8.04%, a trade-off comes as open-circuit voltage (VOC) and fill factor (FF) decreases. Similarly, decreasing the deposition temperature and time improves the device’s ability to collect photons at a lower wavelength (<520 nm), which increases the JSC, but reduces VOC and FF. Recommendations are made to further investigate the effect of varying other deposition parameters on the performance of the device, which may lead to the improvement of the overall performance.